Postopek za odmero davka in pravna sredstva - Kerševan, Erik (Podjetje in delo, 2014)
The decision of the Constitutional Court in the case of the annulled Act on Real Estate Tax represents a final break with a too widely spread belief that law cannot limit the wide discretion of Government and National Assembly when it comes to regulating and enforcing taxes, neither by the general principles of the law nor systemic rules and demands regarding decision-making on legal obligations of individuals and legal entities. Mistakes made by responsible authorities, including e.g. the discrepancy between the basis for real estate taxation from the real value of the given property itself, can in the absence of appropriate procedural rules that guarantee the rights to fair proceedings from Article 22 of the Constitution and effective legal remedy from Article 25. of the Constitution, lead to serious infringement of the right to private property with imposition of the real estate tax, which should not be repeated again in the future.
Keywords: davki; lastnina; nepremičnine; tax